DAMPAK MEDIA DIGITAL SMART BOARD TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Roni Sonjaya; Agus Muharam; Gemi Gustiani; Ihsan Rizali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of science and technology demands innovation in the learning process at elementary schools, particularly in the Natural and Social Sciences (IPAS) subject, which is still largely taught conventionally, resulting in low active student participation. One learning media innovation that has emerged is the SMART BOARD, a digital technology-based interactive whiteboard that enables the delivery of material in a more visual, interactive, and engaging way. This study aims to determine the impact of using SMART BOARD learning media on student learning outcomes in the IPAS subject at the elementary school level. The method used is a quantitative approach with a quasi-experimental design, specifically the Non-Equivalent Control Group Design, involving 56 fourth-grade students of SDN Barunagri, divided into an experimental class (using the SMART BOARD) and a control class (using conventional methods). Data were collected through learning outcome tests, student response questionnaires, and learning activity observation sheets, then analyzed using the Normality test, N-Gain test, and Independent t-test. The results showed that the average posttest score of the experimental class reached 88.37, much higher than that of the control class (64.29). The N-Gain value of the experimental class fell into the high category (0.8013), indicating a significant improvement in learning outcomes. The independent t-test yielded a significance value of 0.000 (p < 0.05), leading to the rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (H₁). Thus, the use of SMART BOARD learning media has a significant and more effective impact on improving student learning outcomes in the IPAS subject compared to conventional learning. These findings are expected to serve as a reference for teachers and schools in developing technology-based learning media.